The Relationship of Demographical Factors on University Students’ Coping Strategy - Aprezo Pardodi Maba; Kusmawati Hatta (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
This study examined the relationship between demographical factors and coping strategies in higher education students. A total of 606 students from a large public university in the Indonesia completed a survey that included measures of demographical variables (such as gender, age, living area, siblings, spending in a month, part-time job, and living arrangement) and coping strategies (such as problem focused, emotional focused, and disengagement). The results of the study indicated that having a part-time job was significantly correlated with coping strategies, in particularly problem-focused coping and emotion-focused coping. While gender, age, living area, siblings, spending in a month, and living arrangement, were not observed to be significantly correlated with coping strategies. The findings of this study have a crucial implications for understanding the relationship of demographical factors affect coping strategy in university students. Furthermore, these findings may inform the development of interventions to support university students’ mental health. Future research should consider employing participants from various background and a longitudinal design to comprehensively understand the relationship between demographical factors and coping strategy in university students.